Food public markets as cultural capital: Girona province - Nadia, Fava; García Vergara, Marisa (International Planning History Society Proceedings, 2016)
The role of public market halls in European cities has been analysed from several perspectives: as specific places for feeding the city; as public services; as the first public places built specifically for women; as places to control health and taxes on food; as places where the urban-rural relationship can be articulated; as places to control citizens’ behaviour, or as places providing local trade within a structure. There are fewer studies exploring public food markets as cultural and social capital with a view to improving the local and new-endogenous economy, an economy which not only involves the environment, but also the sociality linked to the tradition of food production. Research on public markets in small provincial towns is scarce, particularly the role they play in maintaining the urban-rural relationship by providing a local food supply, and also in constructing the rural landscape. This case study concerns the province of Girona and its nine public markets halls. The aim of the study is to explore their role as a public service within the territory and the agricultural landscape, the communication system, the local gastronomic culture and economic culture, this apparently being more resilient and stable than the economy of scale.